Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1089/vio.2019.0067
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women: A Not in My Back Yard (NIMBY) Phenomenon

Abstract: This study investigated the social and cultural representations that employees of the Municipality of Naples hold concerning violence against women. The aim of this research was to explore if and how they attribute blame for gender-based violence and their perception of the effectiveness of resolution strategies focused on either preventing or actively combating violence against women. Their results showed that when respondents attribute violence to sociocultural factors, they recognize the importance of imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Regarding the management of violence perpetrators, both the study interviewees and earlier research [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 58 ] found no differences in operators’ representations based upon their gender. This study considers and discusses factors related to how the gender identity of gender violence intervention personnel could influence their professional interactions with both victims and perpetrators.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Regarding the management of violence perpetrators, both the study interviewees and earlier research [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 58 ] found no differences in operators’ representations based upon their gender. This study considers and discusses factors related to how the gender identity of gender violence intervention personnel could influence their professional interactions with both victims and perpetrators.…”
Section: Discussionmentioning
confidence: 63%
“…In particular, a specific professional background is essential in detecting seemingly invisible and unsuspected gender violence [ 35 , 36 , 37 ], as well as when assisting men in acknowledging the causes and effects of their actions and inviting them to find new strategies to express their negative emotions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The feelings of fear and anger of the staff towards the perpetrators as well as their collusion with the “denial modality” of the perpetrators of violence could lead professionals to develop an attitude of refusal towards them, on the contrary, to minimize their violent acts as previously significantly highlighted by Creazzo [ 46 ] and Esposito et al [ 80 ]. The criminalization of perpetrators and a social unawareness about gender-based violence are in fact the two ineffective options assumed by the literature [ 46 ] behind this helpless repetitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…As far as relational dynamics are concerned, roles, prejudices and gender stigma, shared and passed down in families and contexts have been highlighted [26,82]. So has the reproduction of violent behavior endured or observed as "normality of the phenomenon" [66,83].…”
Section: Discussionmentioning
confidence: 99%